2014
DOI: 10.1155/2014/250523
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intermittent Positive Pressure Ventilation on Depth of Anaesthesia during and after Isoflurane Anaesthesia in Sulphur-Crested Cockatoos (Cacatua galerita galerita)

Abstract: This study aimed to determine the effect of intermittent positive pressure ventilation (IPPV) on the depth of inhalation anaesthesia in parrots. Anaesthesia was induced with 3.0% isoflurane in six Sulphur-crested Cockatoos (Cacatua galerita galerita) and maintained using either 1.5% or 3.0% during spontaneous ventilation (SV) or IPPV at 6 (IPPV-6) or 12 (IPPV-12) breaths per minute. The time taken for the appearance of somatic reflexes and the return of SV after IPPV was recorded. During recovery, the body jer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
0
6
0
3
Order By: Relevance
“…Extreme care should be exercised when anesthetics are administered either by an inhalation or by an injectable route [ 2 ]. The objective of anesthesia is to maintain the possible lowest level of anesthetic to obtain restrain, to minimize stress, to mitigate pain nociception, and to induce muscle relaxation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extreme care should be exercised when anesthetics are administered either by an inhalation or by an injectable route [ 2 ]. The objective of anesthesia is to maintain the possible lowest level of anesthetic to obtain restrain, to minimize stress, to mitigate pain nociception, and to induce muscle relaxation [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In rats, the increase in end-tidal CO 2 concentration at MAC of halothane, isoflurane, and desflurane decreased dose-dependent (Brosnan et al 2007). Chemonges (2014) observed that intermittent pressure ventilation in cockatoos (Cacatua) leads to an increase in isoflurane-dependent dose anesthetic depth.…”
Section: Discussionmentioning
confidence: 99%
“…No que se refere aos valores de PAS, os mesmos ficaram dentro dos limites propostos para outras espécies de aves, apesar da diferença no modo de aferição utilizado entre os pinguins do presente estudo e as aves dos estudos comparativos (LICHTENBERGER, 2005;ACIERNO et al, 2008;ZEHNDER et al, 2009 MITCHELL; RODE, 1990;ESCOBAR et al, 2009;ESCOBAR et al, 2011;CHEMONGES, 2012), interferindo no valor da CAM a ser obtido. Apesar do benefício, a ventilação controlada pode desencadear efeitos hemodinâmicos negativos, resultantes da diminuição do retorno venoso, fazendo-se necessário uma monitoração constante dos valores de pressão arterial e ETCO2 (NAGANOBU; HAGIO, 2000).…”
Section: Etapa 1 -Determinação Da Camunclassified
“…A pressão instituída na ventilação controlada é uma variável importante para o sucesso do procedimento. Em aves, os valores utilizados têm variado entre 4 e 10 cmH2O conforme a espécie (NAGANOBU; HAGIO, 2000;EDLING et al, 2001;CHEMONGES, 2012;ESCOBAR et al, 2012). No presente estudo, os pinguins-de-Magalhães foram ventilados com uma pressão limitada em 10 cmH2O.…”
Section: Etapa 1 -Determinação Da Camunclassified
See 1 more Smart Citation